Agricultural Ecosystem in China: A Case-based Practitioner’s Perspective - Liu, Haoming; Wang, Haolin; Qin, Lijian; Hao, Yajie; Ma, Guoxin (INTI International University, 2020)
Although sustainable agriculture and food systems have appeared to start generating increasing scholarly and policy-maker interest since the 1950s (Pretty, 2008), the very idea creating some level of sustainability in agriculture can be traced back to ancient writings in China (Li, 2001). Despite scholarly and policy efforts, the growing population which in turn results in increasing demands for food and other agricultural products while minimising potentially negative impacts on earth and the environment has remained as a major challenge for this century (Godfray et al., 2010; Sanaullah et al. 2020). With the growing literature on agricultural ecosystems and sustainability in farming, and despite practitioners being an important of the community, there has been insufficient discussion on the practitioners’ views grounded in experiences. Accordingly, this paper provides an account of case-based practitioner’s experiences in China.